Phonetic Symbols through Audiolingual Method to Improve the Students’ Listening Skill - Samawiyah, Zuhrotun; Saifuddin, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
Abstract:Phonetic symbols present linguistic feature to recognize how the words are pronounced or even spelled. While learning English, difficult words are sometimes found because here English is a foreign language with which students often face. In that case, these words might bother the students’ understanding. Obviously, the students were expected to develop their listening skill. It is because listening is one of the English language skills. To enhance the students’ listening skill needs appropriate and effective way. Phonetic symbols were applied in this research to give the students clear input and understanding toward English words. Moreover, these phonetic symbols were applied within audio-lingual method that it provided repetition, memorization, and drills through audio media. This research used Classroom Action Research (CAR) design. The objective of this research was to improve the students’ listening skill through phonetic symbols applied within audio-lingual method. The instruments used were observation and test. Based on the observation, the result showed that the students were encouraged to identify spoken words based on phonetic symbols. They were able to differentiate phonetic symbols used that helped them to identify words on spoken text. Meanwhile, the result of test showed that there were 30 students of 40 students who achived the passing grade, 75. The percentage of students’ achivement test met the target of this research success that was 75% of the students got score ≥ 75. Thus, it can be concluded that phonetic symbols applied in audio-lingual method successfully improved the students’ listening skill.Keywords: Phonetic symbol, Listening skill, Audio-lingual Method